Remoteness, urbanization and child nutrition in sub-Saharan Africa - Headey, Derek D.; Stifel, David; You, Liangzhi; Guo, Zhe (International Food Policy Research Institute, 2017)
Reducing undernutrition requires improving access to goods and services from a wide range of economic and social sectors, including agriculture, education and health. Yet despite broad agreement on the multisectoral nature of the global burden of undernutrition, relatively little research has analyzed how different dimensions of accessibility, such as urbanization and travel times to urban centers, affect child nutrition and dietary outcomes. In this paper we study these relationships in sub-Saharan Africa, a highly rural continent still severely hindered by remoteness problems. We link spatial data on travel times to 20,000 person cities to survey data from 10,900 communities in 23 countries. We document strong negative associations between nutrition indicators and rural livelihoods, but only moderately strong associations with remoteness to cities. Moreover, the harmful effects of remoteness and rural living largely disappear once education, wealth, and social/infrastructural services indicators are added to the model. This implies that the key nutritional disadvantage of rural populations stems chiefly from social and economic poverty. Combating these problems requires either an acceleration of urbanization processes, or finding innovative cost-effective mechanisms for extending basic services to isolated rural communities.